1899 Fla. Laws 280 § 33 - (:unkn) unknown (General Publisher, 1899)
Granted the city council the authority to regulate the storage of gun powder, tar, pitch, resin, saltpeter, gun-cotton, coal oil, and all other combustibles, explosives, and inflammable materials. Also the use of lights, candles, lamps, and steam pipes in all stables, shops, and other places.
--
Keywords: GUN POWDER STORAGE